Uji Coba Pembelajaran “Berpikir Kreatif” Mata Pelajaran IPS Sebagai Media Implementasi Kurikulum Berbasis Kompetensi di Sekolah Dasar - Asmadi Alsa (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2004)
The current study explore whether or not a creative learning model can serve as the media for implementing a competency-based curriculum. More specifically, this study test the model as it is implemented in elementary school social studies class. Competency based curriculum is designed to enhance a more exciting learning experience, to develop creative thinking and to provide necessary life skills for students. This way, students are expected to gain core competence as a result of their learning (i.e. social studies in this research). The participant of this study were teachers and students in three elementary school in the city of Martapura, Kalimantan, and one elementary school in Banjarmasin, Kalimantan. This study used an action research design. In this design, teachers were trained to apply creative learning model every once a week for a consecutive 8 weeks. After the learning model implementation, data were gathered by using interview, observation and documentation. Results of the study show that 1). The Model is feasible to be applied as the media for competency based curriculum 2). More fun and exciting experience shows up in the learning process 3). Students were actively involved in the class 4). Students creativity was facilitated in their learning 4). Life skills were facilitated and appeared in the learning process. The indicators of each finding are discussed in more details in this study report.Keywords: Competency Based Curriculum, Learning Model, Creative Thinking